Comparison of three criteria for overweight and obesity classification among adolescents from southern Brazil - Silva,Diego Augusto Santos (2017)
Abstract AIM To estimate the prevalence of the classifications of overweight and obesity in adolescents according to three criteria for nutritional status classification (Conde & Monteiro, International Obesity Task Force - IOTF and Word Health Organization - WHO), and to investigate whether sociodemographic factors associated with overweight and obesity differ among the three criteria. METHOD cross-sectional study with 1,132 adolescents (14-19 years old) living in Brazil. Body Mass Index (BMI) was classified according to three criteria for nutritional status. A self-administered questionnaire was used to collect sociodemographic information. Sexual maturation was measured by self-reported Tanner stage ratings. Multinomial logistic regression was used to estimate the Odds Ratio and 95% confidence intervals. RESULTS The prevalence of the classification “overweight” (from here on referred to simply as “overweight”) was 23.1% for WHO; 23.7% for Conde & Monteiro criteria: and 19.2% for IOTF. Both boys and girls aged 17-19 were more likely to be overweight using the WHO and Conde & Monteiro criteria than those using the IOTF criteria. Girls in the post-pubertal maturational stage were less likely of being overweight or obese using the three criteria. CONCLUSION The three criteria result in different prevalence measures, with WHO and Conde and Monteiro criteria being more approximate in terms of prevalence and correlated factors when compared to IOTF criteria.